Typology of eating episodes in children and adolescents with overweight/obesity. (January 2022) - Goldschmidt, Andrea B.; Mason, Tyler B.; Smith, Kathryn E.; Egbert, Amy H.; Engel, Scott G.; Haedt-Matt, Alissa
Abstract: Background: Research suggests that youth with overweight/obesity can be subtyped according to disinhibited eating tendencies. No research has attempted to subtype classes of eating episodes along sensational, psychological, and hedonic dimensions. Methods: Youth ( N  = 39; 55% female) aged 8–14 y with overweight/obesity completed a 2-week ecological momentary assessment protocol in which they reported on all eating episodes and their sensational, environmental, affective, and interpersonal contexts. Latent profile analysis (LPA) was used to classify episodes based on loss of control (LOC) while eating, self-reported overeating, food palatability, hunger, and cravings. Classes were compared on affective, interpersonal, appearance-related, and environmental correlates using Wald chi-square tests. Results: LPA identified three classes of eating episodes involving high levels of LOC/self-reported overeating ("binge-like" class), low levels of hunger ("eating-in-the-absence-of-hunger" class), and high hunger and cravings ("appetitive eating" class). Binge-like eating was associated with the highest levels of body dissatisfaction, interpersonal distress, and positive affect, and was most likely to occur in the after-school hours. Conclusions: Binge-like eating tends to occur in a psychological context relative to other types of eating episodes in youth with overweight/obesity. Future research should explore whether certain classes of eating episodes are associated with distinct weight trajectories over time. Highlights: We used latent profile analysis (LPA) to identify classes of eating episodes. Classes were "binge" eating, eating-in-the-absence-of-hunger, and appetitive eating. Classes differed on environmental and psychological correlates.